1974
DOI: 10.1084/jem.140.1.253
|View full text |Cite
|
Sign up to set email alerts
|

Selective Roles of Thymus-Derived Lymphocytes in the Antibody Response

Abstract: Our preceding studies indicated that thymus-derived lymphocytes (T cells) primed with a carrier antigen suppressed antibody responses by bone marrowderived lymphocytes (B cells) against a hapten coupled to the homologous carrier, when they were transferred into immunized recipients (1). The degree of suppression in IgM and IgG antibody responses differed depending primarily on the time when suppressor T cells were transferred to the recipients. Thus, it appeared that susceptibility of B cells to the regulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

1974
1974
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Our previous publications (1,2) reported that passive transfer of thymocytes and spleen cells from mice primed with a carrier antigen suppresses the anti- body response of normal syngeneic hosts against a hapten coupled to the homologous carrier . This suppression was found to be clearly antigen specific, and mediated by T cells primed by the carrier antigen .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous publications (1,2) reported that passive transfer of thymocytes and spleen cells from mice primed with a carrier antigen suppresses the anti- body response of normal syngeneic hosts against a hapten coupled to the homologous carrier . This suppression was found to be clearly antigen specific, and mediated by T cells primed by the carrier antigen .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous publications (1,2) indicated that thymocytes and spleen cells of mice that had been immunized with a high dose of carrier antigen, when transferred into syngeneic host, could suppress the antibody response against a hapten coupled to the homologous carrier . This suppressive effect was found to be mediated by a population of thymus-derived lymphocytes, whose activity was completely abrogated by the treatment with anti-B and complement .…”
mentioning
confidence: 99%
“…In contrast, when these cells were transferred after immunization with DNP-KLH, antibody formation was not inhibited. These results demonstrated that a peripheral T-cell response was suppressing immunologic response to immunization (50,51). This phenomenon was studied extensively in the 1970s and 1980s, and Castagnoli et al found that the supernatant from antigen-specific suppressive thymoma cells was capable of suppressing an alloreactive response to the same antigen.…”
mentioning
confidence: 78%
“…Somatic mutation of germ line-derived variable region genes has been shown to be involved in the generation of high-affinity binding sites for subsequent selection by antigen [10]. T cells can control the production of high-and low-affinity responses [37,38], with CD8+ cells playing an important role in the regulation of affinity maturation [39]. Interferon-gamma (IFNy) (compared with IL-1 which only increases antibody levels) has been shown to potentiate antibody affinity in mice, indicatr ing a role played by Thi cells, possibly acting by enhancing MHC class II expression [40].…”
Section: Discussionmentioning
confidence: 99%